The Demiurge, the Cave, the Dome, and the Monochrome: Psychology of Awakening in The Truman Show and Pleasantville - Chen Tsz Kei (Lecture Notes in Education Psychology and Public Media, 2026)
This paper investigates the cognitive and psychological explanations for the acceptance of false realities and the process of awakening in the films Pleasantville and The Truman Show. Through a literature review of Plato's Allegory of the Cave, Gnosticism, media theory, and psychology, along with a comparative case analysis of the two films, this study explores why individuals remain committed to constructed worlds even in the presence of contradictions. The findings indicate that awakening is more than the acquisition of knowledge. Psychological mechanisms, including confirmation bias, biased assimilation, cognitive dissonance, and fear conditioning, contribute to the maintenance of false realities by influencing responses to anomalous information. Specifically, these cognitive processes can delay, resist, or reinterpret new information. This paper's interdisciplinary approach of connecting theology, philosophy, film analysis, and cognitive psychology can contribute to a deeper understanding of belief formation, perception, and the dismantling of established worldviews.